Efeitos nos pregões eletrônicos de uma instituição de ensino superior após a regulamentação da pesquisa de preços e da formação do preço de referência - Alves, Joice Gaspary (2019)
Public procurement has the function of supplying public agents with goods and services necessary to carry out their activities. For the accurate development of these purchases, there is a vast legislation in Brazil that regulates each process The Federal Constitution of 1988, in its Article 37, item XXI, made express the requirement of bidding for the purchases of the public administration. After that, laws that governed the bidding process emerged, which required the research of prices before any bidding, so that public agencies had a reference value to guide the decisions at what price to contract, seeking to achieve the principle of the most advantageous proposal. However, these laws did not specify how the research should be done, nor how the prices found in it should be treated to form the estimated bid value. As a result, numerous bidding processes became unsuccessful, leading to deserted, failed and partially successful bids.Thus, Normative Instructions (NIs) nº 05/2014 and 03/2017 came to regulate the price research and formation of the reference value, in order to approximate the estimated price to the real market value. At that, the objective was to identify the effects, in terms of effectiveness and economy, on the electronic auction of a superior education institution, arising from the regulations presented by the NIs.The study was carried out through a qualitative research as to the approach; applied as to nature; descriptive and exploratory as to the objectives; The procedures adopted were characterized as bibliographic, documentary and case study. It was analyzed a sample of 320 electronic auctions, from 2012 to 2019, divided into 3 periods, the 1st comprising 2 years before the NI 05/2014, the 2nd covering the years between one NI and another, and the last covering 2 years after. on NI 03/2017.First, it was evaluated each process, from each period, as a whole, in which each was classified as completed with full efficacy, partial efficacy or no efficacy. In a second moment, only the items and their results were considered, and no longer the auction process, being made a single quantitative per period. Still in the analysis on effectiveness, it was investigated, from those auctions sessions with partial effectiveness and without effectiveness, the reasons for their non-award. Economicity was verified by the difference between the estimated total values and the total awarded values. The main results pointed out that after the issue of the NIs: the institution studied had greater effectiveness in its electronic auction sessions, as it had a higher number of auction sessions with total effectiveness and a larger number of awarded items; it was obtained greater savings, both in relation to the discounts achieved and the savings generated with the smaller number of items needing to be rebid; The most significant reason for non-awards was that all the amounts offered were above the price estimated by the administration. Finally, it can be inferred that the period governed by the 1st NI was technically more effective and economical than the period governed by the 2nd NI.